Antibacterial Activity of Drosera Sp. Ethanolic Extract Against Staphylococcus Aureus ATCC 25923 - Krisnawan, Alfian Hendra; Islamie, Ridho; Putri, Rahma Dhianitasari Wahyu; Dewi, Ni Putu Citra Ratna (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2023)
Drosera sp. is an insectivorous plant with secondary metabolites, including naphthoquinones which can be used as antibacterial agents. Staphylococcus aureus is a bacterium that often causes nosocomial infections, such as ARI. This research aims to determine the antibacterial activity of four Drosera species, namely D. burmannii, D. sessilifolia, D. capillaris, and D. filiformis, against Staphylococcus aureus ATCC 25923. The agar diffusion method was employed in antibacterial testing by measuring the inhibition zone. The inhibition zone measured using a 7,000 ppm concentration of Drosera sp. ethanolic extract was 6.74 ± 0.21 mm, 9.21 ± 0.32 mm, 18.18 ± 0.60 mm, and 15.67 ± 0.37 mm for D. burmannii, D. sessilifolia, D. capillaris, and D. filiformis, respectively. The largest value was produced by D. capillaris which was close to 19.73 ± 0.55 mm from the positive control (chloramphenicol). The four Drosera sp. extracts have antibacterial potential against Staphylococcus aureus ATCC 25923.Keywords – Antibacterial activity, Drosera sp., Staphylococcus aureus